G178 What Do GPs and Bereaved Parents Think About Paediatric Oncologists and Palliative Care?. (4th June 2013) - Neilson, SJ; Clifford, C; Gibson, F; Greenfield, SM
Abstract : Aim: The aim of the study was to examine the experiences of bereaved parents and general practitioners (GPs) following the death of a child with cancer within the family home. This presentation focuses on one of the findings; the parent and GP views on the hospital consultants' involvement in the palliative care. Design: A community based qualitative study. Setting: West Midlands region, UK. Participants: Purposeful sample of 18 GPs and 11 bereaved families. The sample was drawn from the families and GPs of children who had been treated for cancer at a regional childhood cancer centre and who subsequently died within the family home. Methods: One-to-one semi-structured tape-recorded interviews were undertaken with GPs and bereaved parents following the death at home of a child with cancer. GPs were contacted three months after the death of the child and the parents at six months. Thematic analysis of the transcriptions was undertaken. Findings: Parents described feeling abandoned at the transition to palliation when management of care transferred to the GP. Families did not perceive a seamless service of medical care between hospital and community. Where offered consultant contact was valued by families and GPs. Text and email were used by families as a means of asking the consultant questions. The GPs lacked role clarity where the consultant continued involvement in the care. Conclusions: The transition to palliation and the transfer of care to community services needs to be sensitively and actively managed for the family and the GP. Medical care between tertiary and primary care should be seen as a continuum. Improving GP: consultant communication could aid role clarity, identify mechanisms for support and advice, and promote the active engagement of the GP in the care. Exploring opportunities for integrated consultant: GP working could maximise mutual learning and support and enhance care provision. The level, access and duration of ongoing contact between consultants and families/GPs require clarity.